Tackifier-free hot melt adhesive composition suitable for use in disposable hygiene articles

JP7645224B2Active Publication Date: 2025-03-13BOSTIK INC +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022500575
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-12
Filing Date
2020-07-10
Publication Date
2025-03-13
Estimated Expiration
2040-07-10

Smart Images

  • Figure 0007645224000001
    Figure 0007645224000001
  • Figure 0007645224000002
    Figure 0007645224000002
  • Figure 0007645224000003
    Figure 0007645224000003
Patent Text Reader

Abstract

The hot melt adhesive composition comprises a polypropylene homopolymer having a DSC melting point below 100°C; a butene-based copolymer; and a plasticizer. The butene-based copolymer may comprise a butene-rich amorphous poly-alphaolefin, such as a butene-propylene copolymer, or a semi-crystalline copolymer, such as a butene-ethylene copolymer. The hot melt adhesive is particularly useful for bonding substrates that swell or stretch significantly during use. Such applications include bonding a superabsorbent polymer to a substrate or bonding together two substrates, at least one of which contains a superabsorbent polymer, such as the top and bottom layers of the absorbent core of disposable hygiene articles, such as diapers, feminine sanitary napkins, and adult incontinence pads. The tackifier-free hot melt adhesive composition exhibits a sufficiently low viscosity as well as an appropriate elongation at break and yield stress to stabilize the absorbent core containing the superabsorbent polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This international patent application claims the benefit under 35 U.S.C. 119(e) of U.S. patent application Ser. No. 62 / 873,259, filed July 12, 2019.

[0002] The present invention relates to a tackifier-free hot melt adhesive composition suitable for use in disposable hygiene articles, such as diapers and training pants. The adhesive is particularly well suited for applications requiring high elongation at break and yield stress without having an excessively high viscosity at the desired application temperature. [Background technology]

[0003] Hot melt adhesives typically exist as solid materials at ambient temperatures, but can be converted to flowable liquids upon the application of heat. These adhesives are particularly useful in the manufacture of various disposable goods that often require bonding of various substrates. Specific applications include disposable diapers, hospital pads, feminine sanitary napkins, panty shields, surgical drapes, and adult incontinence briefs (collectively referred to as disposable nonwoven sanitary products). Other miscellaneous applications include paper products, packaging materials, automobile headliners, appliances, tapes, and labels. In most of these applications, the hot melt adhesive is heated to its molten state and then applied to a substrate (often referred to as the primary substrate). A second substrate (often referred to as the secondary substrate) is then immediately brought into contact with and pressed against the first substrate. Upon cooling, the adhesive solidifies and creates a strong bond. A major advantage of hot melt adhesives is the absence of a liquid carrier, as is the case with water-based or solvent-based adhesives, thereby avoiding the use of costly processes to remove the solvent.

[0004] In many applications, hot melt adhesives are often extruded directly onto a substrate in the form of a thin film or beads by using piston or gear pump equipment. In this case, the substrate is placed in intimate contact with a heated die under pressure. The temperature of the die must be maintained well above the melting point of the adhesive to allow the molten hot melt material to flow smoothly out of the discharge nozzle. Most applications, especially those encountered in the manufacture of food packaging and disposable nonwoven hygienic articles, often involve bonding delicate and heat-sensitive substrates, such as plastic films of thin dimensions. This defines the upper coating temperature limit for hot melt adhesive applications. Today's commercially available hot melts are typically formulated to have a coating temperature below 200°C to avoid burning or deformation of the substrate. Along with direct coating, some indirect or non-contact coating methods have also been developed, whereby the hot melt adhesive can also be spray-coated onto the substrate using compressed air. These non-contact coating techniques include conventional swirl spray, Signature™, Control Coat™, UFD™ and various forms of meltblowing processes. However, indirect processes require that the adhesive have a sufficiently low viscosity at the application temperature to produce an acceptable coating pattern, typically in the range of 2,000-30,000 mPa·s, and often in the range of 2,000-15,000 mPa·s.

[0005] Hot melt adhesives are traditionally composed of polymers, plasticizers, tackifying resins (also referred to herein as "tackifiers") and optional additives such as waxes and wax antioxidants. Tackifiers have long been considered an essential component of hot melt adhesives. Traditionally, the role of tackifiers using styrene block copolymer systems is to increase the glass transition temperature of the adhesive system, thereby improving tack. Tackifiers further help to control the viscosity of the final formulation. However, tackifiers can be viewed in a negative light because they can introduce odor and volatile organic compounds (VOCs) into the adhesive formulation.

[0006] Efforts have been made to develop hot melt adhesives that do not contain tackifiers. For example, US Patent No. 9,139,755 discloses a hot melt adhesive composition that includes about 90-10% by weight of an amorphous polyolefin copolymer composition that includes 50-70% by weight of 1-butene; about 10-90% by weight of a heterophasic polypropylene copolymer composition that includes propene and a comonomer that includes ethylene, 1-hexene, or 1-octene, and that includes amorphous properties and crystalline blocks; and about 0.1-30% by weight of a polyisobutylene plasticizer made with AlCl3, where the adhesive provides cohesion from the heterophasic polypropylene copolymer and adhesive strength from the amorphous polyolefin copolymer.

[0007] Additionally, U.S. Pat. No. 8,623,480 discloses a hot melt adhesive composition comprising a first polymer consisting of a non-functionalized amorphous polyalpha-olefin polymer comprising at least 55% by weight, and more than about 50% by weight, of polypropylene; a second polymer selected from the group consisting of polypropylene homopolymers, propylene copolymers, and combinations thereof; a functionalized polypropylene wax; and a polyethylene wax (preferably without a tackifier).

[0008] WO 2013 / 039261 discloses a hot melt adhesive comprising: (A) a propylene homopolymer having a melting point of 100° C. or less, obtained by polymerizing propylene using a metallocene catalyst; and (B) an ethylene-based copolymer. Summary of the Invention

[0009] There remains a need in the art for adhesives that have low tack, sufficiently high elongation at break and high yield stress to withstand the swelling of superabsorbent polymers when wet, and also have suitable viscosity at the desired application temperature.

[0010] It would therefore be advantageous to provide a hot melt adhesive that would overcome the shortcomings of the prior art adhesives mentioned above. In particular, it would be desirable to make a hot melt adhesive that does not contain a tackifier. Such an adhesive would desirably be polyolefin-based, since such adhesives can handle high temperatures well and are generally recognized to have low odor. Such an adhesive would have a high enough elongation at break and high yield stress to withstand the swelling of superabsorbent polymers when wet, and would also have a suitable viscosity at the desired application temperature. Such an adhesive would be particularly suitable as a microfibrillated adhesive, alone or in combination with other adhesives and / or cellulose fibers, and would serve to contain superabsorbent polymers (SAPs) in hygiene articles, such as diapers. The adhesive would not need to have a high level of tack, but would be required to have very good elongation to accommodate the SAP as it swells / elongates. The challenge in making a tackifier-free adhesive is to develop a formulation that is low enough in viscosity to process, but is "strong" enough to meet the mechanical properties, such as elongation at break.

[0011] In view of the shortcomings of the prior art, the present invention provides a hot melt adhesive composition comprising a polypropylene homopolymer having a DSC melting point below 100° C., a 1-butene-based copolymer, and a plasticizer, but no tackifier. Such a composition provides both high elongation at break and yield stress, but has a sufficiently low viscosity to be processable.

[0012] According to one embodiment of the present invention, a method for making a laminate comprises the steps of applying the hot melt adhesive composition of the present invention in a molten state to a first substrate; and laminating the second substrate to the first substrate by contacting the second substrate with the adhesive composition.

[0013] According to another embodiment of the present invention, an absorbent core comprises a first layer and a second layer, at least one of the first layer and the second layer comprises a superabsorbent polymer, and the first layer and the second layer are adhered to each other by a hot melt adhesive composition of the present invention, and the adhesive composition adheres to the superabsorbent polymer in the absorbent core.

[0014] According to another embodiment of the present invention, a disposable hygiene article comprises an absorbent core of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In the present invention, the hot melt adhesive composition comprises a polypropylene homopolymer having a DSC melting point of less than 100°C; a 1-butene-based copolymer; and a plasticizer, the adhesive being free of tackifiers. Such compositions provide both high elongation at break and yield stress, but have a sufficiently low viscosity to be processable. Such adhesives are particularly suitable for applications requiring the ability to have significant elongation (e.g., up to 400%) in use, and provide high yield stress (e.g., at least 0.5 MPa), while having a relatively low viscosity, e.g., less than about 30,000 centipoise (cP) at 163°C (325°F) and less than about 17,500 centipoise (cP) at 177°C (350°F).

[0016] The polypropylene homopolymer used in the present invention has a DSC melting point of less than 100°C, more preferably between 60°C and 90°C. As used herein, "DSC melting point" refers to the melting point measured using differential scanning calorimetry (DSC) according to ASTM E-794-01. The weight average molecular weight of the polypropylene homopolymer is preferably about 5,000 to about 150,000 daltons, preferably about 30,000 to about 90,000 daltons, and most preferably about 35,000 to about 85,000 daltons. As used herein, when referring to the weight average molecular weight of any component herein, the weight average molecular weight is determined by gel permeation chromatography using a polypropylene standard.

[0017] The exemplified type of polypropylene homopolymer was developed by Idemitsu Petrochemical, Ltd. This type of polymer is described as its L-MODU grade, which is an abbreviation for low molecular weight and low modulus polyolefin. Although they are entirely polypropylene based, they do not have the properties normally associated with polypropylene. Regular polypropylene homopolymers tend to have very high crystallinity and melting points. This is true whether they are produced using Ziegler-Natta or metallocene catalyst technology. The L-MODU grades are produced using metallocene catalysts that control the stereoregularity of the polymer. This results in polymers that give properties that were previously unattainable. For example, the melting points of these novel polymers are significantly lower than any other polypropylene homopolymers produced with metallocene catalysts. A typical polypropylene homopolymer has a melting peak of about 130°C to 170°C as measured by differential scanning calorimetry according to ASTM E794-01. The L-MODU polymers have a ring and ball softening point of less than 130° C. as measured according to ASTM E-28-99. They have a melting point of less than 100° C., more preferably between 60° C. and 90° C., as measured by Differential Scanning Calorimetry (DSC) method according to ASTM E794-01.

[0018] The process for making these polymers is described in U.S. Pat. No. 6,797,774 (assigned to Idemitsu Petrochemical Co., Ltd, Tokyo, Japan) along with various hot melt adhesive formulations. Because they have such low melting points and long recrystallization times, special considerations are required to process them using underwater pelletizing equipment. This is described in U.S. Pat. No. 7,776,242 (assigned to Idemitsu Petrochemical Co., Ltd, Tokyo, Japan). The disclosures found in U.S. Pat. Nos. 6,797,774 and 7,776,242 are both specifically incorporated herein by reference.

[0019] Although the L-MODU polymers are polypropylene homopolymers, they are, as mentioned above, very different from conventional polypropylene polymers. In addition to having extremely low melting points as measured by DSC, their melting enthalpy values ​​are also much lower than conventional polypropylene grades. Analysis according to ASTM E793-01 "Standard Test Method for Enthalpies of Fusion and Crystallization by Differential Scanning Calorimetry" gave the results shown in Table 1 below. A slight modification was made for this test, using a scan temperature of 20°C / min instead of 10°C / min.

[0020] [Table 1]

[0021] Both the melting peak value and the melting enthalpy value are extremely low compared to most conventional polypropylene-based homopolymers. Typical polypropylene homopolymers have melting points of about 130°C to 171°C and melting enthalpy values ​​of about 80 J / g or more. L-MODU polymers have a unique combination of melting points and melting enthalpies. However, to produce a hot melt adhesive suitable for the desired application using these materials as the base polymer requires the use of an additional polymer, i.e., a 1-butene-based copolymer.

[0022] The hot melt adhesive composition of the present invention further comprises a 1-butene-based copolymer. As used herein, the term "butene-based" copolymer means that the copolymer comprises more than 50 mol% butene and is made from at least one other monomer in addition to butene. In one embodiment of the present invention, the 1-butene-based copolymer comprises a butene-rich amorphous poly-alphaolefin. As used herein, the term "butene-rich" copolymer means that the copolymer comprises more than 50 mol% butene. As used herein, amorphous poly-alphaolefin (APAO) refers to a type of low molecular weight amorphous propylene copolymer with butene and at least one other monomer, typically produced using Lewis acid catalysts. Preferably, the 1-butene-rich amorphous poly-alphaolefin comprises a butene-propylene copolymer. In another embodiment, the 1-butene-based copolymer comprises a semi-crystalline copolymer. Preferably, the semi-crystalline copolymer comprises a butene-ethylene copolymer. In yet another embodiment, the 1-butene based copolymer comprises a blend of a butene-rich amorphous poly-alphaolefin and a semi-crystalline copolymer.

[0023] Generally, the weight average molecular weight of the 1-butene-based copolymer is preferably from about 15,000 to about 160,000 daltons, preferably from about 40,000 to about 150,000 daltons, and most preferably from about 45,000 to about 145,000 daltons. In some embodiments in which the 1-butene-based copolymer comprises a butene-rich amorphous poly-alphaolefin, the weight average molecular weight of the butene-rich amorphous poly-alphaolefin is from about 15,000 to about 85,000 daltons, preferably from about 40,000 to about 65,000 daltons, and most preferably from about 45,000 to about 60,000 daltons.

[0024] The hot melt adhesive composition of the present invention further comprises a plasticizer. The plasticizer may be any known compatible plasticizer, preferably selected from the group consisting of mineral oils, synthetic poly-alpha olefin oils and polyisobutylene. Suitable plasticizers may also be selected from the group consisting of olefin oligomers and low molecular weight polymers, as well as vegetable and animal oils and their derivatives. Petroleum-based oils that may be employed are relatively high boiling materials containing only a small proportion of aromatic hydrocarbons. In this regard, aromatic hydrocarbons should preferably be less than 30%, more preferably less than 15%, of the oil, measured as the proportion of aromatic carbon atoms. More preferably, the oil is substantially non-aromatic. The oligomers may be polypropylene, polybutene, hydrogenated polyisoprene, hydrogenated polybutadiene, and the like, having an average molecular weight between about 350 g / mole and about 10,000 g / mole. Suitable vegetable and animal oils include glycerol esters of common fatty acids and their polymerization reaction products.

[0025] Other useful plasticizers can be found within the group of commonly used dibenzoates, phosphates, phthalate esters, as well as esters of mono- or polyglycols. Examples of such plasticizers include, but are not limited to, dipropylene glycol dibenzoate, pentaerythritol tetrabenzoate, 2-ethylhexyl diphenyl phosphate, polyethylene glycol 400-di-2-ethylhexoate; butyl benzyl phthalate, dibutyl phthalate, and dioctyl phthalate. The plasticizers found to be useful in the present invention can be any number of different plasticizers, but the inventors have found that mineral oils and liquid polybutenes having an average molecular weight of less than 5,000 Daltons are particularly advantageous. As will be appreciated, plasticizers have typically been used to reduce the viscosity of the overall adhesive composition without substantially reducing the adhesive strength and / or the use temperature of the adhesive, as well as to extend the open time and improve the flexibility of the adhesive.

[0026] In some embodiments of the present invention, the polypropylene homopolymer is present in an amount of about 20% to about 75% by weight, preferably about 25% to about 65% by weight, and most preferably about 30% to about 60% by weight, based on the total weight of the composition; the 1-butene-based copolymer is present in an amount of about 3% to about 50% by weight, preferably about 4% to about 45% by weight, and most preferably about 5% to about 35% by weight, based on the total weight of the composition; and the plasticizer is present in an amount of about 20% to about 60% by weight, preferably about 25% to about 55% by weight, and most preferably about 30% to about 40% by weight, based on the total weight of the composition.

[0027] In some embodiments of the present invention, the weighted average of the weight average molecular weights of the polypropylene homopolymer and butene-based copolymer is from about 60,000 to about 80,000 Daltons, preferably from about 64,000 to about 76,000 Daltons, and most preferably from about 66,000 to about 74,000 Daltons. The weighted average of the weight average molecular weights of the polymers is determined by adding the product of the weight fraction of each polymer (based on the total weight of the polymers) and its weight average molecular weight.

[0028] The present invention may optionally include an antioxidant (also called a stabilizer). When included, the antioxidant may be present in an amount of about 0.1% to about 3% by weight of the total adhesive composition. It is preferred that about 0.2% to 2% of the antioxidant is incorporated into the composition. The antioxidants useful in the hot melt adhesive composition of the present invention are incorporated to help protect the above-mentioned polymers, and thus the entire adhesive system, from the effects of thermal and oxidative degradation that typically occurs during the manufacture and application of the adhesive, as well as during normal exposure of the final product to the ambient environment. Among the applicable antioxidants, high molecular weight hindered phenols and multifunctional phenols, such as sulfur and phosphorus-containing phenols, are preferred. Hindered phenols are well known to those skilled in the art and are characterized as phenolic compounds that contain sterically bulky groups in the vicinity of the phenolic hydroxyl group. In particular, typically, a tertiary butyl group is substituted in at least one position that is ortho to the phenolic hydroxyl group on the benzene ring. The presence of these sterically bulky substituents in the vicinity of the hydroxyl group helps to suppress the stretching frequency and therefore its reactivity. This steric hindrance therefore confers stabilizing properties to the phenolic compounds.Representative hindered phenols include: 1,3,5-trimethyl-2,4,6-tris(3-5-di-tert-butyl-4-hydroxybenzyl)benzene; pentaerythritol tetrakis-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; n-octadecyl-3(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; 4,4'-methylenebis(4-methyl-6-tert-butylphenol); 2,6-di-tert-butylphenol; 6-(4-hydroxyphenoxy)-2,4-bis(n-octylthio)-1,3,5-triazine; 2,3,6-tris(4-hydroxy-3,5-di-tert-butyl-phenoxy)-1,3,5-triazine; di-n-octadecyl-3,5-di-tert-butyl-4-hydroxybenzylphosphonate; 2-(n-octylthio)ethyl-3,5-di-tert-butyl-4-hydroxybenzoate; and sorbitol hexa-3(3,5-di-tert-butyl-4-hydroxy-phenyl)propionate.

[0029] The performance of these antioxidants can be further improved by using in combination with: (1) synergists, such as thiodipropionate esters and phosphites; and (2) chelating agents and metal deactivators, such as ethylenediaminetetraacetic acid, its salts and disalicylalpropylenediimine.

[0030] It should be understood that other optional additives may be incorporated into the adhesive composition of the present invention to modify certain physical properties. These include, for example, inert coloring materials such as titanium dioxide, fillers, fluorescent agents, UV absorbers, surfactants, other types of polymers, etc. Typical fillers include: talc, calcium carbonate, clay, silica, mica, wollastonite, feldspar, aluminum silicate, alumina, hydrated alumina, glass microspheres, ceramic microspheres, thermoplastic microspheres, barite, and wood flour. Surfactants are particularly important in disposable nonwovens for hygiene, because they can dramatically reduce the surface tension of the adhesive applied to, for example, the core of the diaper, thereby allowing for more rapid transfer of urine and subsequent absorption by the core.

[0031] In some embodiments of the present invention, the adhesive composition includes a wax. Such waxes include low molecular weight waxes, petroleum waxes such as paraffin wax, synthetic waxes, and polyolefin waxes. The adhesive composition is substantially free of wax, e.g., preferably less than 1% by weight, more preferably less than 0.5% by weight, and most preferably no wax, based on the total weight of the composition.

[0032] In some embodiments of the present invention, the hot melt adhesive composition consists essentially of a polypropylene homopolymer having a DSC melting point of less than 100° C.; a 1-butene-based copolymer; and a plasticizer, and the composition does not include a tackifier. In a further embodiment of the present invention, the hot melt adhesive composition consists essentially of a polypropylene homopolymer having a DSC melting point of less than 100° C.; a 1-butene-based copolymer; and a plasticizer, and the composition does not include a tackifier. By not including a tackifier, the composition does not contain a tackifier or includes only a minimal amount of tackifiers known in the art for use in hot melt adhesives (e.g., those disclosed in U.S. Patent Application Publication No. 10,011,744, which is incorporated herein by reference). Such tackifier types include: aliphatic and alicyclic petroleum-based hydrocarbon resins; aromatic petroleum-based hydrocarbon resins and their hydrogenated derivatives; hydrocarbon resins derived from aliphatic / aromatic petroleum systems and their hydrogenated derivatives; aromatic modified alicyclic resins and their hydrogenated derivatives; polyterpene resins having a softening point of about 10° C. to about 140° C.; copolymers and terpolymers of natural terpenes; natural and modified rosins; glycerol and pentaerythritol esters of natural and modified rosins; and phenolic modified terpene resins.

[0033] The hot melt compositions of the present invention are further characterized by having low viscosities as measured at 163°C (325°F) and 177°C (350°F) using a Brookfield viscometer with spindle 27 according to ASTM-D3236. The spindle speed was adjusted to provide a percent torque of about 45-90%. The viscosity of the composition is preferably about 30,000 centipoise (cP) or less at 163°C (325°F), more preferably about 22,500 centipoise (cP) or less at 163°C (325°F), and most preferably about 15,000 centipoise (cP) or less at 163°C (325°F). The viscosity of the composition is preferably about 17,500 centipoise (cP) or less at 177°C (350°F), preferably about 15,000 centipoise (cP) or less at 177°C (350°F), and most preferably about 12,500 centipoise (cP) or less at 177°C (350°F). In an embodiment of the invention, the heat of fusion of the composition obtained by DSC according to ASTM E793-01 is less than 40 J / g, preferably less than about 35 J / g, more preferably less than about 25 J / g, even more preferably less than about 20 J / g, and most preferably less than about 15 J / g. In an embodiment of the invention, the composition has a yield stress of at least about 0.5 MPa, preferably at least about 0.7 MPa, and most preferably at least about 0.9 MPa. The yield stress is determined by mechanical properties determined by Instron. In an embodiment of the invention, the composition has an elongation at break of at least about 350%, preferably at least about 375%, more preferably at least about 390%, and most preferably at least about 400%, as determined by the Elongation Test described in the Examples below.

[0034] This combination of properties has been found to be particularly suitable for use in stabilizing absorbent cores containing superabsorbent polymers. Included in the present invention is any combination of the above range limits of viscosity, yield stress, and elongation at break. For example, in one embodiment of the present invention, the adhesive has a viscosity of about 22,500 centipoise (cP) or less at 163°C (325°F) and about 15,000 centipoise (cP) or less at 177°C (350°F), a yield stress of at least about 0.9 MPa, and an elongation at break of at least about 390%.

[0035] The hot melt adhesive composition of the present invention can be compounded by using various mixing methods known in the art. A representative mixing procedure includes placing all ingredients in a jacketed mixing kettle equipped with a rotor and then raising the temperature of the mixture to a range of 150°C to 200°C to melt the contents. Any of the components can be pre-blended or added individually to the mixing kettle. For example, the polymers can be preformed mixtures or blends or added individually to the mixing kettle. It should be understood that the exact temperature used in this step will depend on the melting points of the particular components. Mixing is continued until a consistent homogenous mixture is produced. The contents of the kettle are protected with an inert gas, such as carbon dioxide or nitrogen, throughout the mixing process. Various additives and modifications can be made to the procedure of the present invention to produce hot melt compositions without departing from the spirit of the present invention, such as applying a vacuum to facilitate the removal of entrapped air. Other equipment useful for compounding the compositions of the present invention includes, but is not limited to, single or twin screw extruders or other types of extruder machines, kneaders, intensive mixers, Ross™ mixers, etc. The hot melt adhesive is then cooled to room temperature and formed into chubs or pellets with a protective coating on the surface for shipment and use.

[0036] The adhesive composition of the present invention can be used as a general purpose hot melt adhesive in many applications, such as, for example, disposable nonwoven hygiene articles, paper converting, flexible packaging, woodworking, carton and case sealing, labeling and other assembly applications. Particularly preferred applications include nonwoven disposable diaper and feminine sanitary napkin constructions, diaper and adult incontinence brief elastic accessories, diaper and napkin core stabilization, diaper backsheet laminates, industrial filter material processing, surgical gown and surgical drape combinations, and the like.

[0037] The hot melt adhesive so obtained can be applied to a substrate using a variety of application techniques, including hot melt glue gun, hot melt slot die coating, hot melt wheel coating, hot melt roller coating, melt blow coating, swirl spray, contact or non-contact strand coating (commercially available as Signature™, Control Coat™, UFD™), etc. In one preferred embodiment, the hot melt adhesive is applied directly onto the substrate.

[0038] In one embodiment of the invention, a method of making a laminate includes the steps of: (1) applying the hot melt adhesive composition of the invention in a molten state to a first substrate; and (2) laminating the second substrate to the first substrate by contacting the second substrate with the adhesive composition. In one embodiment of the invention, the first substrate comprises a first layer (e.g., bottom layer) of an absorbent core, and the second substrate comprises a second layer (e.g., top layer) of an absorbent core, at least one of the first layer or the second layer having a superabsorbent polymer associated therewith. The first substrate and the second substrate are a single continuous material, but may be folded, whereby the two folded portions form the first and second substrates.

[0039] Any suitable absorbent core comprising a superabsorbent polymer can be used in the context of the present invention. Suitable absorbent cores are described in US Patent Application Publication No. 2017 / 0209616; US Patent Application Publication No. 2017 / 0165133; and US Patent Application Publication No. 2016 / 0270987, all of which are incorporated herein by reference. As described in US Patent Application Publication No. 2017 / 0165133, the absorbent core structure typically includes an absorbent polymer material, such as a hydrogel-forming polymer material (also called absorbent gelling material (AGM)) or a superabsorbent polymer (SAP). This absorbent polymer material allows the absorbent article to absorb and trap large amounts of bodily fluids, such as urine, during use, resulting in less re-wetting and better skin dryness. Reducing or eliminating the cellulose or cellulosic fibers traditionally used in the absorbent core structure allows for thinner absorbent core structures to be made. To maintain the mechanical stability of these absorbent core structures, a fiberized net structure (which may optionally be an adhesive) may be added to stabilize the absorbent polymer material. The absorbent core may have additional adhesives to support the fiberized net structure adhesive and / or to bond with each other, other core materials and / or other article components. The superabsorbent polymer material may be deposited on or combined with the first and second substrates such that the fiberized net structure coats the superabsorbent polymer material on the respective first and second substrates.

[0040] In an embodiment of the present invention, the fiberized netting structure comprises the adhesive composition of the present invention. The fiberized netting structure may contain other substances, such as other adhesives or cellulose fibers. In another embodiment of the present invention, the only adhesive used in the fiberized netting structure is the adhesive composition of the present invention. Furthermore, in another embodiment of the present invention, the fiberized netting structure consists only of one or more adhesive compositions of the present invention. In one embodiment of the present invention, the first and second absorbent layers are bonded together, at least a portion of the fiberized netting structure of the first absorbent layer is in contact with at least a portion of the fiberized netting structure of the second absorbent layer, and the adhesive of the present invention used in the fiberized netting structure bonds the two layers together to form an absorbent core. In an embodiment of the present invention, both the first layer and the second layer of the absorbent core have a superabsorbent polymer associated therewith. In another embodiment of the present invention, only one of the layers has a superabsorbent polymer associated therewith.

[0041] In another embodiment of the method of making the laminate of the present invention, the first substrate is a first layer of an absorbent core, and the second substrate is a superabsorbent polymer. The superabsorbent polymer is deposited on the first layer, and then the adhesive composition is applied. In this embodiment, the adhesive is capable of forming a fiberized net on and adjacent to the superabsorbent polymer, which is then further bonded to the first layer. In a further embodiment, the second layer is formed in the same manner, and then the two layers are laminated together, and the adhesive is cooled to form the absorbent core.

[0042] Aspects of the invention 1. A hot melt adhesive composition comprising: Polypropylene homopolymer having a DSC melting point below 100°C; 1-butene-based copolymers; and Plasticizer and wherein the hot melt adhesive composition does not include a tackifier. The composition of embodiment 1, wherein the 2.1-butene-based copolymer comprises a butene-rich amorphous poly-alphaolefin. 3. The composition of embodiment 2, wherein the 1-butene rich amorphous poly-alphaolefin comprises a butene-propylene copolymer. 4. The composition of any one of aspects 1-3, wherein the 1-butene-based copolymer comprises a semi-crystalline copolymer. 5. The composition of embodiment 4, wherein the semi-crystalline copolymer comprises a butene-ethylene copolymer. 6. the polypropylene homopolymer is present in an amount of about 20% to about 75% by weight, preferably about 25% to about 65% by weight, and most preferably about 30% to about 60% by weight, based on the total weight of the composition; The 1-butene-based copolymer is present in an amount of about 3% to about 50% by weight, preferably about 4% to about 45% by weight, and most preferably about 5% to about 35% by weight, based on the total weight of the composition; and The composition of any of aspects 1-5, wherein the plasticizer is present in an amount of about 20% to about 60% by weight, preferably about 25% to about 55% by weight, and most preferably about 30% to about 40% by weight, based on the total weight of the composition. 7. The weight average molecular weight of the polypropylene homopolymer is about 5,000 to about 150,000 daltons, preferably about 30,000 to about 90,000 daltons, and most preferably about 35,000 to about 85,000 daltons; and The composition according to any one of the first to sixth aspects, wherein the weight average molecular weight of the 1-butene-based copolymer is from about 15,000 to about 160,000 daltons, preferably from about 40,000 to about 150,000 daltons, and most preferably from about 45,000 to about 145,000 daltons. 8. 1-Butene-based copolymers include butene-rich amorphous poly-alphaolefins including butene-propylene copolymers; The weight average molecular weight of the polypropylene homopolymer is about 5,000 to about 150,000 daltons, preferably about 30,000 to about 90,000 daltons, and most preferably about 35,000 to about 85,000 daltons; and The composition according to any one of the first to sixth aspects, wherein the butene-rich amorphous poly-alphaolefin has a weight average molecular weight of about 15,000 to about 85,000 daltons, preferably about 40,000 to about 65,000 daltons, and most preferably about 45,000 to about 60,000 daltons. 9. The composition of any one of aspects 1 to 8, wherein the weighted average of the weight average molecular weight of the polypropylene homopolymer and butene-based copolymer is from about 60,000 to about 80,000 daltons, preferably from about 64,000 to about 76,000 daltons, and most preferably from about 66,000 to about 74,000 daltons. 10. The composition of any of the preceding aspects, wherein the viscosity of the composition is about 30,000 centipoise (cP) or less at 163° C. (325° F.), preferably about 22,500 centipoise (cP) or less at 163° C. (325° F.), and most preferably about 15,000 centipoise (cP) or less at 163° C. (325° F.). 11. The composition of any of the preceding aspects, wherein the viscosity of the composition is about 17,500 centipoise (cP) or less at 177° C. (350° F.), preferably about 15,000 centipoise (cP) or less at 177° C. (350° F.), and most preferably about 12,500 centipoise (cP) or less at 177° C. (350° F.). 12. The composition of any one of aspects 1-11, wherein the composition has a heat of fusion of less than 40 J / g, preferably less than about 35 J / g, more preferably less than about 25 J / g, more preferably less than about 20 J / g, and most preferably less than about 15 J / g, as measured by DSC according to ASTM E793-01. 13. The composition of any one of aspects 1-12, wherein the plasticizer is selected from the group consisting of mineral oil, synthetic poly-alpha olefin oil, and polyisobutylene. 14. The composition of any one of aspects 1-13, further comprising an antioxidant. 15. The composition of any one of aspects 1 to 14, which does not contain a wax. 16. The composition of any of the preceding aspects, having an elongation at break of at least about 350%, preferably at least about 375%, and most preferably at least about 390%. 17. The composition of any of the preceding aspects, having a yield stress of at least about 0.5 MPa, preferably at least about 0.7 MPa, and most preferably at least about 0.9 MPa. 18. A method of making a laminate comprising the steps of: applying the hot melt adhesive composition according to any one of aspects 1 to 17 in a molten state to a first substrate; and laminating a second substrate to the first substrate by contacting the second substrate with the adhesive composition. The method includes: 19. The method of embodiment 18, wherein the first substrate comprises a first layer of an absorbent core and the second substrate comprises a second layer of an absorbent core, and at least one of the first layer or the second layer has a superabsorbent polymer associated therewith. 20. An absorbent core comprising a first layer and a second layer, at least one of the first layer and the second layer comprising a superabsorbent polymer, and the first layer and the second layer are adhered to one another by a hot melt adhesive composition according to any one of aspects 1-17, and the superabsorbent polymer forms an absorbent core. 21. A disposable hygiene article comprising an absorbent core according to embodiment 20. EXAMPLES

[0043] The present invention is further illustrated by the examples set forth below.

[0044] To prepare the hot melt adhesive, all the components, i.e., polymer, plasticizer, and antioxidant, were weighed into an aluminum pint can and heated to 177°C under nitrogen (5 scfh). The overhead mixer's double blade impeller was lowered into the aluminum can and mixed at 200 rpm at constant temperature until homogenous. Compounding is complete when the mixture is homogenous and no lumps from the polymer are evident. The compounding can then be used to test viscosity, tensile properties, and / or to make laminates to test final performance.

[0045] Adhesives were made using the ingredients listed below and shown in Tables 2 and 3. The numbers listed in Tables 2 and 3 are weight percentages for the raw materials and should equal 100%.

[0046] CALSOL 5500 is a naphthenic process oil (available from Calumet Specialty Products).

[0047] Spectrasyn 40 is a liquid poly-alpha olefin used as a synthetic oil (available from ExxonMobil).

[0048] INDOPOL H-100 is a polyisobutene oligomer (available from Ineos Capital Ltd.).

[0049] L-MODU S600 is a low modulus, controlled stereoregularity polypropylene homopolymer (available from Idemitsu Kosan Co., Ltd.)

[0050] L-MODU S901 is a low modulus, controlled stereoregularity polypropylene homopolymer (available from Idemitsu Kosan Co., Ltd.)

[0051] VESTOPLAST 508 is a butene-rich (1-butene-co-propylene) copolymer (available from Evonik Industries).

[0052] VESTOPLAST 704 is a propene-rich copolymer (available from Evonik Industries).

[0053] ENGAGE 8137 is an ethylene-octene copolymer (available from Dow).

[0054] KOATTRO PB M8911M is a 1-butene copolymer (available from LyondellBasell Industries Holdings).

[0055] KOATTRO 8510 is a 1-butene copolymer (available from LyondellBasell Industries Holdings).

[0056] IRGAFOS 168 is tris(2,4-di-tert-butylphenyl)phosphate (available from BASF Chemicals) and is used as an antioxidant.

[0057] IRGANOX 1010 is pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (available from BASF Corp.) and is used as an antioxidant.

[0058] [Table 2]

[0059] Viscosity was measured according to ASTM D3236 at 149, 163 and 177°C using spindle 27. The spindle speed was adjusted so that the percent torque was between 45% and 90%. Viscosity was low enough to spray, i.e., less than about 30,000 cP at 163°C.

[0060] Dumbbells for tensile testing were molded by pouring the molten adhesive into a silicone mold such that the overall length of the dumbbell was 3.5" x 1.0" with a thickness of 0.125" overflowing the mold. The test area of ​​the dumbbell was 0.5" x 0.5". A heated spatula was used to scrape excess adhesive from the silicone mold to make the dumbbell as close to 0.125" thick as possible. The samples were allowed to cool to room temperature for at least 12 hours before testing for elongation at break, maximum stress, and other mechanical tests. The top and bottom of the dumbbell were clamped into an Instron tensile tester so that only the 0.5" x 0.5" test area was exposed. The pulling rate was 2" / min and the specimen was pulled until it broke. If the adhesive can withstand the pulling caused by the SAP particles swelling, the elongation at break ("elongation test") is recorded as a percentage based on the difference between the final length and the initial length divided by the initial length. The goal was to obtain an adhesive that would maintain elongation of approximately 400% or more.

[0061] The yield stress is automatically calculated from both the % elongation and yield stress values ​​by BlueHill3 Software provided by Instron.

[0062] Patterning quality was determined qualitatively and quantitatively. The adhesive was heated to approximately 170°C and pumped through a hose to a Signature Low Flow Nozzle (Nordson Corp.) at a line speed of 200 ft / min to a coat weight of 5 gsm. The air flow rate was adjusted to give the most fiberized pattern in appearance with minimal agglomerates (having a size greater than about twice the average size of the droplets) or minimal flying adhesive strands (qualitative). If the adhesive was unable to produce an acceptable pattern at 170°C, the temperature was increased up to a maximum of 190°C. The application temperature is preferably below 180°C. On average, the air was anywhere from 10 psi to 40 psi, which is meant only as a guide, not a rule, as it depends on the settings of each piece of equipment. The nozzle head was located 20 mm above the first substrate (33 gsm spunbond nonwoven). The second substrate was a release liner, which could make the analysis of the samples easier. Qualitative analysis was performed by measuring the diameter of the fibers obtained upon spray application using a microscope. The goal was to produce a fiber diameter of less than 60 μm, preferably less than 30 μm. The tensile properties of the adhesive are a function of the fiber diameter, so the desired fiber diameter may vary depending on the adhesive formulation, the desired properties, and other conditions.

[0063] The embodiment of the invention shown in Table 2 uses a 1-butene-based copolymer that is a butene-rich amorphous poly-alpha olefin. Example 1 shows one embodiment of the formulation of the invention with all the ingredients required to produce a product with sufficiently low viscosity (desired less than about 30,000 cP at 163° C.) and elongation at break in a tensile test (about 400% or more). Example 1 produced an average fiber diameter of 20 μm when applied at 5 gsm at 170° C. using a Signature Low Flow Nozzle (available from Nordson). Comparative Example 1 uses a propene-rich amorphous poly-α-olefin (APAO) instead of the 1-butene-rich APAO (Example 1), resulting in an elongation at break that is too low to be practical, although it maintains an acceptable viscosity. Comparative Example 2 uses an ethylene-octene copolymer instead of the 1-butene-rich APAO of Example 1. Comparative Example 2 produced an acceptable elongation at break, but had a viscosity at 163° C. that was too high to process. Example 2 shows another embodiment of the invention, in which liquid poly-isobutene is used as the plasticizing component. Example 2 has a higher, but still suitable viscosity for processing, and the elongation at break is further improved.

[0064] Alternative embodiments of the formulations of the present invention use semi-crystalline 1-butene rich copolymers in place of the 1-butene rich APAO and are shown in Table 3, Examples 3-6.

[0065] [Table 3]

[0066] All of Examples 3-6 provided formulations with adequate elongation at break and good, if not outstanding, yield stress values. Only the formulation of Example 4 provided an adhesive with a viscosity slightly higher than the preferred range, but this is still within the scope of the invention. Example 3 provided an average fiber diameter of 22 μm when applied at 5 gsm at 190° C. using a Signature Low Flow Nozzle (available from Nordson).

[0067] Where a range of values ​​is given, it is understood that each intermediate value between the upper and lower limits of that range, and various combinations or subcombinations of intermediate values, as well as various other stated or intermediate values ​​in that stated range, are included within the stated range of values. In addition, the invention includes the component at the lower limit of a first range and the upper limit of a second range.

[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. All publications and patents specifically mentioned herein are incorporated by reference in their entirety for all purposes, including describing and disclosing the chemicals, instruments, statistical analyses and methodologies described therein that may be used in connection with the present invention. All references cited herein should be taken as indicative of the level of skill in the art. Nothing herein should be taken as an admission that the present invention is not entitled to backdate such disclosure by virtue of prior invention.

[0069] Although illustrated and described herein with reference to certain specific embodiments, it is nevertheless not intended to limit the invention to the details shown, but rather various modifications in the details may be made within the scope and range of equivalents of the claims and without departing from the spirit of the invention.

Claims

1. 1. A hot melt adhesive composition comprising: (a) a polypropylene homopolymer having a DSC melting point of less than 100° C.; (b) a 1-butene-based copolymer; and (c) Plasticizer and wherein the hot melt adhesive composition does not include a tackifier.

2. 10. The composition of claim 1, wherein the 1-butene based copolymer comprises a butene-rich amorphous poly-alphaolefin.

3. 3. The composition of claim 2, wherein the 1-butene rich amorphous poly-alpha olefin comprises a butene-propylene copolymer.

4. The composition of claim 1 , wherein the 1-butene-based copolymer comprises a semi-crystalline copolymer.

5. The composition of claim 4, wherein the semi-crystalline copolymer comprises a butene-ethylene copolymer.

6. the polypropylene homopolymer is present in an amount of 20% to 75% by weight, based on the total weight of the composition; The 1-butene-based copolymer is present in an amount of 3 wt% to 50 wt%, based on the total weight of the composition; and The composition of claim 1, wherein the plasticizer is present in an amount of from 20% to 60% by weight, based on the total weight of the composition.

7. The weight average molecular weight of the polypropylene homopolymer is from 5,000 to 150,000 Daltons; and The composition of claim 1, wherein the 1-butene-based copolymer has a weight average molecular weight of 15,000 to 160,000 Daltons.

8. The 1-butene based copolymers include butene-rich amorphous poly-alphaolefins including butene-propylene copolymers; The weight average molecular weight of the polypropylene homopolymer is from 5,000 to 150,000 Daltons; and 2. The composition of claim 1, wherein the butene-rich amorphous poly-alpha olefin has a weight average molecular weight of 15,000 to 85,000 Daltons.

9. 10. The composition of claim 1, wherein the weighted average of the weight average molecular weight of the polypropylene homopolymer and the butene-based copolymer is from 60,000 to 80,000 Daltons.

10. 10. The composition of claim 1, wherein the composition has a viscosity of less than or equal to 30,000 centipoise (cP) at 163°C (325°F).

11. 10. The composition of claim 1, wherein the composition has a viscosity of less than or equal to 17,500 centipoise (cP) at 177°C (350°F).

12. 10. The composition of claim 1, wherein the composition has a heat of fusion of less than 40 J / g as measured by DSC according to ASTM E793-01.

13. 2. The composition of claim 1, wherein the plasticizer is selected from the group consisting of mineral oil, synthetic poly-alpha olefin oil, and polyisobutylene.

14. The composition of claim 1 further comprising an antioxidant.

15. The composition of claim 1 which does not contain a wax.

16. 10. The composition of claim 1 having an elongation at break of at least 350%.

17. 10. The composition of claim 1 having a yield stress of at least 0.5 MPa.

18. 1. A method of making a laminate comprising the steps of: applying the hot melt adhesive composition according to any one of claims 1 to 17 in a molten state to a first substrate; and laminating a second substrate to the first substrate by contacting the second substrate with the adhesive composition. The method includes:

19. 20. The method of claim 18, wherein the first substrate comprises a first layer of an absorbent core and the second substrate comprises a second layer of the absorbent core, and at least one of the first layer or the second layer has a superabsorbent polymer associated therewith.

20. 18. An absorbent core comprising a top layer and a bottom layer, at least one of the top layer and the bottom layer comprising a superabsorbent polymer, and the top layer and the bottom layer are adhered to each other by a hot melt adhesive composition according to any one of claims 1 to 17, and the adhesive composition adheres the superabsorbent polymer within the absorbent core.

21. A disposable hygiene article comprising an absorbent core according to claim 20.

Citation Information

Patent Citations

  • Hot-melt adhesive composition

    JP1989282280A

  • hot melt adhesive

    JP2017504688A

  • Hot-melt adhesive for straw-added container

    JP2018030918A

  • Hot melt adhesive

    JP2019011422A

  • Absorbent article with tackifier-free adhesive

    JP2019022662A